Six-Year Experience of Outpatient Total and Completion Thyroidectomy at a Single Academic Institution. Issue 4 (April 2017) - Frank, Ethan; Park, Joshua; Simental, Alfred; Vuong, Christopher; Lee, Steve; Filho, Pedro Andrade; Kwon, Daniel; Liu, Yuan
Outpatient thyroidectomy has become slowly accepted with various published reports predominantly examining partial or subtotal thyroidectomy. Concerns regarding the safety of outpatient total and completion thyroidectomy remain, especially with regard to vocal fold paralysis, hypocalcemia, and catastrophic hematoma. We aimed to evaluate the safety of outpatient thyroid surgery in a large cohort by retrospectively comparing outcomes in those who underwent outpatient (n = 251) versus inpatient (n = 291) completion or total thyroidectomy between February 2009 and February 2015. Outpatient completion and total thyroidectomy had lower rates of temporary hypocalcemia (6% vs 24.4%; P < 0.001) and no significant difference in rates of return to emergency department (1.2% vs 1.4%), hematoma formation (0.8% vs 0.7%), temporary (2% vs 4.1%) or permanent (0.4% vs 0.7%) vocal fold paralysis, or permanent hypocalcemia (0.4% vs 0%) compared with the inpatient group. Outpatients requiring calcium replacement had shorter duration of postoperative calcium supplementation (44.4 ± 59.3 days vs 63.3 ± 94.4 days; P < 0.001). Our data demonstrate similar safety in outpatient and inpatient total and completion thyroidectomy.